The long and winding road: Labour market integration of refugees in Norway - Inés Hardoy; Tao Zhang (University of Oslo, Department of Economics, 2019)
Large waves of refugees have arrived in Europe on a regular basis in recent decades. We know little about the impact of labour market policies intended to improve the labour market integration of refugees and their reunited family members. Using rich longitudinal data from Norway of the past 30 years, we study the impact of different labour market programs for refugees and their reunited families. We find no lock-in effects while the program is in process. On the contrary, program participation seems to function as a springboard to working life. Work practice seems to be particularly suitable for refugees to enhance employability while training enhances ordinary education. Wage subsidies do not seem to have the desired impact and can be an indication that it may have been used too early in the integration process.
Keywords: C41; J22; J61; J68; 330; refugees; labour market programs; effect evaluation; time-of-event analysis